Genetic characterization of a Clostridium difficile erythromycin-clindamycin resistance determinant that is transferable to Staphylococcus aureus. - Hächler, H (1987)
The transferable macrolides-lincosamides-streptogramin B (MLS) resistance determinant of clinical isolates of Clostridium difficile, designated ermZ, has been shown to share homology with ermB, which is associated with Staphylococcus aureus transposon Tn551. Homology within Tn551 was confined to less than or equal to 1.3 kilobases, whereas no homology could be demonstrated between Tn551 sequences external to ermB and MLS-resistant C. difficile. Transfer of ermZ from C. difficile to S. aureus was achieved by means of the filter mating technique, suggesting that (conjugative?) intergeneric exchange between clostridia and staphylococci may also occur in nature. S. aureus transcipients were shown to contain additional DNA from C. difficile besides ermZ. This additional DNA appeared to be present in MLS-susceptible C. difficile and might form part of an as yet undemonstrated insertion sequence element associated with ermZ of resistant strains.